2009
DOI: 10.1021/jp8092012
|View full text |Cite
|
Sign up to set email alerts
|

Structural Analysis of Human Serum Albumin Complexes with Cationic Lipids

Abstract: Human serum albumin (HSA) is a major transporter for delivering several endogenous compounds including fatty acids in vivo. Even though HSA is the primary target of fatty acid binding, the effects of cationic lipid on protein stability and conformation have not been investigated. The aim of this study was to examine the interaction of human serum albumin (HSA) with helper lipids--cholesterol (Chol) and dioleoylphosphatidylethanolamine (DOPE)--and with cationic lipids--dioctadecyldimethylammonium bromide (DDAB)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
130
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(144 citation statements)
references
References 39 publications
12
130
0
Order By: Relevance
“…The number of steroid imidazolidines per DNA 'n' calculated [37] for (7-9) was found to be 1.13, 1.19 and 1.07, respectively indicating that compound 8 has higher DNA binding propensity in agreement with the absorption titration experiment.…”
Section: F = C T (F/f O -P) (1 -P)supporting
confidence: 64%
“…The number of steroid imidazolidines per DNA 'n' calculated [37] for (7-9) was found to be 1.13, 1.19 and 1.07, respectively indicating that compound 8 has higher DNA binding propensity in agreement with the absorption titration experiment.…”
Section: F = C T (F/f O -P) (1 -P)supporting
confidence: 64%
“…The number of folic acid bound per protein (n) is calculated from log [(F 0 À F)/F] = log K S + n log [folic acid] for the static quenching (Charbonneau, Beauregard, & Tajmir-Riahi, 2009;Froehlich, Mandeville, Jennings, Sedaghat-Herati, & Tajmir-Riahi, 2009;Hasni et al, 2011;Liang, Tajmir-Riahi, & Subirade, 2008;Mandeville & Tajmir-Riahi, 2010). The linear plot of log [(F 0 À F]/ F] as a function of log [folic acid] extracted from Fig.…”
Section: Complexmentioning
confidence: 99%
“…2a and b). It binds various endogenous and exogenous ligands including hormones, fatty acids and foreign molecules such as drugs [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. Recently our group has shown that HSA binds to BA with a binding constant of K BA = 1.685±0.01×10 6 M −1 [24].…”
Section: Introductionmentioning
confidence: 99%